Quality and Acceptability of Dry Fermented Sausages Prepared with Low Value Pork Raw Material. Issue 2 (17th June 2016) - Alves, Susana P.; Fernandes, Maria J.; Fernandes, Maria H.; Bessa, Rui J.B.; Laranjo, Marta; A.‐Santos, Ana Cristina; Elias, Miguel; Fraqueza, Maria J.
Abstract: The food industry aims to produce dry fermented sausages (DFS) with high quality, but Alentejano or Iberian pork has a high price, which might jeopardize the sustainability of traditional producers. Considering this fact, the objective of this work was to evaluate the quality and acceptability of DFS made with low value pork raw material from Alentejano purebred sows and a crossbred Iberian × Duroc pigs. The nutritional fat values, microbial and sensorial quality of DFS with different diameters were assessed and the texture and fatty acids (FA) profiles were correlated with sensory attributes. Pork raw material did not influence pH, a w and microbial characteristics of both DFS, but those produced with Alentejano sows presented the highest content of polyunsaturated FA and less saturated FA. Both DFS presented satisfactory appreciations regarding sensorial quality. Practical Applications: This work aims to increase knowledge about dry fermented sausage processed with an alternative crossbreed Iberian × Duroc pigs less expensive than the Iberian pigs. This alternative in traditional processing of dry fermented sausages with the maintenance of their quality and consumer acceptability will contribute to the sustainability of all traditional small meat industries and of an economic sector with great importance on the Mediterranean region.